Yield stability of ten garlic (Allium sativum) clonal cultivars in northern Patagonia, Argentina - Portela, Jose Antonio; Sidoti Hartmann, Brunilda; Reybet, Graciela E.; Bellaccomo, Maria Carolina; Astorquizaga, Rubén Eduardo (International Society for Horticultural Science, 2021)
Presentado al VI International Symposium on Edible Alliaceae